What is ecology - Wade, Michael V. (Chicago : Encyclopaedia Britannica Educational Corporation, 1977)
Outstanding photography of natural life helps define and illustrate basic terms in the science of ecology. The variety and complexity of plant and animal relationship - a dependance for survival - are explored through several major biomes: forest, desert, seashore, urban, and agricultural. It also considers how human activity presents a constant danger to ecological balance
Keywords: Ecology